2008
DOI: 10.1093/jac/dkn013
|View full text |Cite
|
Sign up to set email alerts
|

The use of trough ribavirin concentration to predict sustained virological response and haematological toxicity in HIV/HCV-co-infected patients treated with ribavirin and pegylated interferon

Abstract: Our study confirmed a relationship between ribavirin exposure and both efficacy and toxicity. Moreover, we found ribavirin C(trough) cut-offs for both SVR in genotypes 1 and 4 and overall haematological toxicity. These findings deserve further clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 21 publications
3
37
1
Order By: Relevance
“…In this perspective, RBV TDM might maintain a role in the management of the prevailing proportion of patients with WT ITPA genotype, in whom RBV concentration may be fruitfully modified by RBV dose adjustment. Because RBV Pk exposure is also associated with the rate of SVR, 6,11,13,27,36,37 the same might also apply to carriers of ITPA variants with suboptimal RBV concentration, in whom RBV dose may be increased with a smaller risk of anemia. In conclusion, this retrospective study confirms the high impact of ITPA SNPs on hemolytic anemia and seems to suggest a cut-off value for trough plasma RBV concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, RBV TDM might maintain a role in the management of the prevailing proportion of patients with WT ITPA genotype, in whom RBV concentration may be fruitfully modified by RBV dose adjustment. Because RBV Pk exposure is also associated with the rate of SVR, 6,11,13,27,36,37 the same might also apply to carriers of ITPA variants with suboptimal RBV concentration, in whom RBV dose may be increased with a smaller risk of anemia. In conclusion, this retrospective study confirms the high impact of ITPA SNPs on hemolytic anemia and seems to suggest a cut-off value for trough plasma RBV concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Repeatedly, individual RBV dose and pharmacokinetic (Pk) exposure have been found to be consistent determinants of treatment-associated anemia, and recommendations on dose reduction have been released in order to mitigate the impact of RBV on the severity of anemia. [6][7][8][9][10] Some other studies have not observed an association between Hb decline and plasma RBV concentrations, when multivariate analyses were performed. [11][12][13] Among the nonmodifiable individual factors also contributing to anemia development in recipients of anti-HCV therapy, single nucleotide polymorphisms (SNPs) in the human DNA region coding for inosine triphosphatase (ITPA) were identified recently as the most significant variables influencing the risk of anemia.…”
Section: Introductionmentioning
confidence: 94%
“…In summary, high baseline HCV RNA, HCV genotype 1 or 4, and C trough of Ͻ2.5 g/ml RBV were found to be indepen- (1,3). These differences may be explained by distinct characteristics of patients that may affect ribavirin pharmacokinetics (age, gender, renal function, body weight, race, and drug and food interactions) and technical aspects regarding the quantification of RBV C trough (day after therapy initiation at which RBV C trough was quantified, time between blood extraction and plasma separation, and methodology for RBV C trough quantification).…”
mentioning
confidence: 86%
“…There has therefore been some interest in the utility of therapeutic drug monitoring in plasma or serum to optimize doses and predict SVRs. Some small studies, mainly retrospective, in co-infected patients have suggested a relationship between week 4 serum or plasma concentrations predicted EVR, SVR, haematological toxicity and relapse [53][54][55][56]. Furthermore, once steady state has been achieved, there is a suggestion that concentrations at 3 and 6 months do not vary greatly in co-infected patients and that these concentrations may influence treatment outcomes [57].…”
Section: Ribavirin Dose Monitoring and Interactionsmentioning
confidence: 99%